Estudio de los procedimientos aplicados en base a la taxonomía del espresso - Conde Calle, María Belén (2024)
Coffee is on the list of the most consumed drinks in the world and the numbers increase every year, considering that the coffee industry is constantly innovating in terms of preparation and service methods; Ecuador is a consumer and producer country par excellence, however, the consumer sector is unaware of the procedures given to the raw materials (coffee and varieties) for the production of espresso-based drinks. The research analyzes the procedures that are applied for the preparation of espresso-based drinks, taking advantage of the favorable reception that this type of drinks have by consumers, part of a documentary analysis of the taxonomy of espresso, aspects that intervene such as the botany of the coffee, traceability, techniques and variables involved in the preparation, the study emphasizes the application in the caturra variety; the objective is to carry out a study of the different parameters used from the taxonomy of espresso and their impact on the final quality in the cup; the research methods applied were inductivedeductive and their respective research tools, such as observation guides in which variables intervene to obtain good quality espresso, technical sheets for the preparation of classic espresso-based drinks were also developed, as well as Likewise, new drinks are proposed based on this product. All of this served to standardize processes and correctly apply variables to obtain espresso base drinks.